Strategi Pengembangan Usaha Jamur Merang di Desaglagahwero Kecamatan Panti Kabupaten Jember - Kurniawan, Deddy; Firdausi, Muhammad Ilham (Program Studi Agribisnis, 2021)
Mushroom (Volvariela Volvacea) is one of the horticultural commodities that can be used for food and neutraceuntics, mushroom cultivation has a bright prospect in Indonesia because of the very supportive natural conditions. Jember Regency is one of the districts that has a large amount of horticultural production, especially mushrooms after watermelon, cayenne pepper, long beans, and cabbage. Human resource development in organizations is an integral form of development effort, both concerning human resources as individuals and as a system, as well as organization as a container for human resources to meet the needs of any organization. The strategy for developing a mushroom business uses a strategy (S-O), namely a strategy to: increase the quality and volume of mushroom production by adding more places of production and seeking cooperation with food processing producers